Female Representation and Violence in the Ceremonial Entries of the Italian Wars. Issue 5 (6th May 2022) - Reid, Elizabeth
Abstract: This essay considers the gendered implications of female representation in the ceremonial entries of the Italian Wars (1494–1559) in light of the events' hyper‐masculine martial context. It takes a holistic approach, uncommon in entry scholarship, by considering the thematic intersections between entry decorations, participation, performance, and commemoration. Visually rendered and embodied performances of political allegory, and written accounts of these displays, reveal an underlying threat of gendered violence. Female personifications of cities, like male‐authored accounts of the cities' women, framed the female body in relation to the male gaze, often to reinforce the entrant's masculinity. This study finds that different modalities of female representation across ceremonial entries utilized allegorical and patriarchal dynamics which were underwritten by the threat of gendered violence.